Lithium isotopes differentially modify mitochondrial amorphous calcium phosphate cluster size distribution and calcium capacity - Deline, Marshall L.; Straub, Joshua; Patel, Manisha; Subba, Pratigya; Grashei, Martin; van Heijster, Frits H. A.; Pirkwieser, Philip; Somoza, Veronika; Livingstone, James D.; Beazely, Michael; Kendall, Brian; Gingras, Michel J. P.; et al. (Frontiers in Physiology, 2023)
Lithium is commonly prescribed as a mood stabilizer in a variety of mental health conditions, yet its molecular mode of action is incompletely understood. Many cellular events associated with lithium appear tied to mitochondrial function. Further, recent evidence suggests that lithium bioactivities are isotope specific. Here we focus on lithium effects related to mitochondrial calcium handling. Lithium protected against calcium-induced permeability transition and decreased the calcium capacity of liver mitochondria at a clinically relevant concentration. In contrast, brain mitochondrial calcium capacity was increased by lithium. Surprisingly, 7Li acted more potently than 6Li on calcium capacity, yet 6Li was more effective at delaying permeability transition. The size distribution of amorphous calcium phosphate colloids formed in vitro was differentially affected by lithium isotopes, providing a mechanistic basis for the observed isotope specific effects on mitochondrial calcium handling. This work highlights a need to better understand how mitochondrial calcium stores are structurally regulated and provides key considerations for future formulations of lithium-based therapeutics.